Wednesday
May 22, 2013

# Homework Help: math

Posted by rick on Sunday, April 8, 2012 at 2:25am.

Let f(x) = ax^3 + bx^2 + 3x – 4. If f(x) is divided by (x – 2), the remainder is 2. When it is divided by (x – 1), the remainder is -2. Find a and b.

• math - Steve, Sunday, April 8, 2012 at 5:34am

f(2) = 2
f(1) = -2

8a + 4b + 6 - 4 = 2
a + b + 3 - 4 = -2

8a + 4b = 0
a + b = -1

so, b = -2a
a = 1
b = -2

f(x) = x^3 - 2x^2 + 3x - 4

Related Questions

math - Let f(x) = ax^3 + bx^2 + 3x – 4. If f(x) is divided by (x – 2...
math - Let f(x) = ax^3 + bx^2 + 3x – 4. If f(x) is divided by (x – 2...
math, algebra - can someone explain to me this please.... What is the difference...
Polynomials - Let f(x) = ax^3 + bx^2 + 3x – 4. If f(x) is divided by (x &#...
Maths - 3 2 If 3x+ax+bx+4 has x+1 as factor and leaves remainder 2 when divided...
Remainder Theorem - Let f(x) = ax^3 + bx^2 + 3x – 4. If f(x) is divided by...
Calculus - Which of the following would have a horizontal asymptote of y = b/a? ...
calc - is the integral of 2x/(x^3-x) =-1/2ln(x+1)+1/2ln(x-1) I got this by doing...
Math - ç 2x^3 + 3x^2 + x + 1 dx --------------------- -2x + 1 [2x^3...
algebra-Am I right so far - Use the quadratic formula to determine the x-...